The Effect of Upper Jakarta Traffic Density on Controller Workload at Jakarta ACC - Leni Harlina Samsuwir; Surya Tri Saputra; Martha Saulina (CV. AFDIFAL MAJU BERKAH, 2026)
The continuous growth of air traffic in Indonesia has significantly increased traffic density, particularly in the Upper Jakarta sector of the Jakarta Flight Information Region (FIR). This increase directly affects the workload of Air Traffic Controllers (ATCs) at the Jakarta Area Control Centre (ACC), who are responsible for maintaining safety and efficiency in air navigation. This study aims to analyze the effect of traffic density on ATC workload at Jakarta ACC. The research employs a quantitative method with a descriptive-analytical approach, focusing on variables such as flight frequency, aircraft concentration, and route complexity. ATC workload is measured using indicators of communication frequency, rerouting actions, and response time. Data were collected through observations, questionnaires, interviews, and operational records from AirNav Indonesia. Statistical analysis, including descriptive analysis and simple regression, was used to assess variable relationships. The results show that increased traffic density significantly raises ATC workload, while experience, working environment, and technological support moderate this effect. The study contributes academically to human factors and air traffic management research and practically provides recommendations for AirNav Indonesia to optimize workload management and enhance aviation safety.